Deposition of polycrystalline Cd1‐xZnx Te films on ZnTe/graphite and graphite substrates by close‐spaced sublimation. Issue 7 (24th March 2014) - Okamoto, Tamotsu; Akiba, Sho; Takahashi, Kohei; Nagatsuka, Satsuki; Kanda, Yohei; Tokuda, Satoshi; Kishihara, Hiroyuki; Sato, Toshiyuki
Abstract: The effects of a ZnTe layer on the deposition of a Cd1‐ x Zn x Te (CZT) layer in the initial stage of the close‐spaced sublimation (CSS) deposition were investigated. The deposition rate was almost constant in the initial stage of the CdTe deposition on the ZnTe/graphite substrates. However, the deposition rate within 1 minute was lower than that after 1 minute in the CdTe deposition on graphite substrates. This result suggests that nucleation of CdTe directly deposited on graphite substrate is difficult when compared to that with a ZnTe layer. Furthermore, the effects of CdCl2 and ZnTe additions to the CdTe sources in the CSS deposition were also investigated. Both the grain size and the intensity of donor‐acceptor pair (DAP) emission in photoluminescence (PL) spectra were decreased by the effect of CdCl2 addition. Zn content in CZT films was controlled by the ZnTe ratio in the CdTe/ZnTe powder sources. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)